Сучасний стан підприємництва в Запорізькій області - Педченко, Анна Павлівна; Педченко, Анна Павловна; Pedchenko, Anna; Власюк, Юлія Олександрівна; Власюк, Юлия Александровна; Vlasiuk, Yuliia (Люкс, 2016)
UK: В статті проведено статистичний аналіз стану підприємництва Запорізької області у 2015 році, зокрема, визначено місце області за основними показниками підприємницької діяльності серед регіонів України. Здійснено розподіл суб’єктів господарювання та підприємств області по основних показниках діяльності. Визначено вплив середніх та малих підприємств на економічний та соціальний розвиток області, розглянуто їх структуру за видами економічної діяльності. Проаналізовано концентрацію підприємств у містах обласного значення та районах Запорізької області, зайнятість та соціальні й економічні показники їх діяльності. Здійснено розподіл прибуткових підприємств області за розміром і видами економічної діяльності у 2015 році. EN: According to statistical analysis of the entrepreneurship condition in Zaporizhia region in 2015, given in the article, it has been defined that in compliance with the key indicators of entrepreneurial activity the region was taken up its place in the top ten among the regions of Ukraine. Business entities and regional enterprises allocation via major activity indices have been implemented. It was determined that enterprises make up 15,3% of all market participants and provide 91,4% of the products realized by them). Thus a significant impact on economic and social development of the region is being carried out by medium and small enterprises providing slightly less than half of the total production volume, works and services, functioning and creating jobs in different spheres of economic activity. The concentration of enterprises in the cities of regional importance and districts in Zaporizhia region, employment, as well as social and economic indicators of these activities have been analyzed. The largest number of businesses per 10 thousand people of current population have been observed in Zaporizhia, Azov and Chernihiv districts, the smallest number - in Kamensko-Dniprovsky district, Tokmak and Energodar; the share of profitable enterprises in the region made up 77.3%. As a result, in 2015 the enterprises in Zaporizhia region got unprofitable financial result before tax, mainly due to unprofitable surplus of large industry enterprises. The distribution made among region enterprises having got profit in 2015 in size and economic activities showed that best results in 2015 among the key economic sectors had been reached by agriculture, forestry and fishery enterprises.
Modern state of entrepreneurship in Zaporizhia region
Keywords: підприємництво; суб’єкт господарювання; фізична особа-підприємець; велике підприємство; середнє підприємство; мале підприємство; Запорізька область; entrepreneurship; entity; individual entrepreneur; large enterprise; medium enterprise; small enterprise; Zaporizhia region